Facial middle-third root fracture. A case report - Daraí Bárbara Sánchez Montero; Nestor Rodríguez Cruz (Medisur)
Horizontal root fracture is a rare dental trauma the general dentist is not always appropriately trained for. This article presents an horizontal root fracture of the facial upper central middle-third with incomplete apical formation in an 8 years old, male patient, who came to our consultation a month after the dental trauma had occurred. The latest procedures, consisting on the exclusive instrumentation and treatment of the coronal segment, and the exclusive use of calcium hydroxide as irrigantion fluid and intracanal medicament by taking profits of its capacity to induce hard tissue were used. This procedure was reactivated every 15 days and clinical-radiographic controls were performed every 3 months to monitor progress in the root apex formation. When apex formation was completed it was decided to seal the root canal with gutta-percha by using the conventional lateral condensation technique. It was decided to publish this case report first of all because it is a condition that, unlike what happened with this specific patient, does not always progress successfully and because an unconventional treatment, with positive results in year and a half was applied.